iTRAQ-based quantitative proteomic profiling of the regulatory mechanisms on immune functions and blood lipids in aged mice fed with Lentinula edodes-derived polysaccharides - Xiaofei Xu; Xiaofei Liu; Jin Chen; Jingjing Guan; Donghui Luo (Food Science and Human Wellness)
The mechanisms of mushroom polysaccharides on immune functions and lipid metabolism of aged mammals have not been fully elucidated. In the present study, after assessing the impacts of one type of Lentinula edodes-derived polysaccharides, named L2, on immune functions and blood lipid profiles, isobaric tags for relative and absolute quantification (iTRAQ)-based proteomic profiling of the small intestinal tissues from aged mice treated with L2 was performed. L2 reversed immune function declines and modulated the lipid metabolism of aged mice evidenced by increased levels of serum TC, HDL-C, and LDL-C, and reduced levels of serum TG. Moreover, a total of 95 differentially regulated proteins (DRPs) were identified, of which 75 were up-regulated and 20 were down-regulated. Most of the DRPs were involved in intracellular and extracellular structure organization, and cellular and metabolic regulation. Particularly, approximately 16 and 9 DRPs participated in the regulation of immune functions and lipid metabolism, respectively. Furthermore, protein-protein interaction analysis highlighted that cadherin-1, plectin, cadherin-17, Ras GTPase-activating-like protein IQGAP2, and ezrin might be key proteins in response to L2 treatment. These findings provide new insights into the biological mechanisms of mushroom polysaccharides in anti-aging from a proteomic perspective.